Zondervan atlas of the Bible - Rasmussen, Carl.; Rasmussen, Carl. (Grand Rapids, Mich. : Zondervan, 2010)
Detailed maps provide information on the geography and history of the Holy Land, and are accompanied by a chronological chart and indexes of references to Scriptures and individuals.
Geographical section. Introduction to the Middle East as a whole -- The geography of Israel and Jordan -- The geography of Egypt -- The geography of Syria and Lebanon -- The geography of Mesopotamia -- Historical section. The pre-patriarchal period -- The patriarchs and the Egyptian sojourn -- Exodus and conquest -- Settlement in the land of Canaan -- Transition to the monarchy : Samuel and Saul -- The united monarchy : David and Solomon -- The divided kingdom -- Judah alone -- Exile and return -- The arrival of the Greeks -- The Maccabean Revolt and the Hasmonean dynasty -- Early Roman rule in Palestine -- The life of Christ -- The expansion of the Church in Palestine -- The journeys of Paul -- The seven churches of Revelation -- Jerusalem -- The disciplines of historical geography.
Revised edition of: Zondervan NIV atlas of the Bible.
Includes bibliographical references and indexes.
Keywords: Bible -- Geography; Bible -- Geography -- Maps; Bible -- History of Biblical events; Bible -- History of contemporary events